Creep behaviour of an Al–Si–Al2O3 composite based on phase evolution at 1300oC. Issue 2 (15th January 2022) - Ma, Chenhong; Li, Yong; Jiang, Peng; Xue, Wendong; Sun, Jialin
Abstract: An Al–Si–Al2 O3 composite was prepared with corundum, aluminium powder and silicon powder. A creep test was carried out at 1300°C under 0.2 MPa for 50 h in air. The results show that the Al–Si–Al2 O3 composite performs a low constant creep rate and remain until the end of the 50-h test. This is attributed to the in-situ formation of the tough non-oxide reinforcements, whisker-like (AlN) x (Al2 OC)1- x solid solution and granular β-SiC, by reactions of Al and Si during creep test. The whisker-like (AlN) x (Al2 OC)1- x solid solution and granular β-SiC reinforcements are evenly filled in the pores, which play the role of bridging and pinning reinforcement, forming a strong network structure with corundum aggregates. Moreover, these non-oxide phases are not wetted by the liquid phases, which impel the liquid phase shrinks in the network structure in isolation during creep test. Thus, the adverse effect of the liquid phase on the high-temperature strength of the composites is eliminated, so the composites with strong network structure quickly get a stationary low-creep state. A creep mechanism model is established.